Potensi Biokimia Aloe vera (L.) Burm.f. sebagai Agen Penyembuhan Luka dan Basis Formulasi Sediaan Topikal Farmasi - Salsabila Rahman; Ardi Mustakim (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Aloe vera (L.) Burm.f. is a bioactive plant containing polysaccharides, anthraquinones, sterols, vitamins, minerals, and glycoproteins, contributing to wound healing through anti-inflammatory, antibacterial, antioxidant mechanisms, fibroblast stimulation, and accelerated re-epithelialization. This study employed a systematic literature review (SLR) of 37 peer-reviewed articles (2018–2025) to evaluate the biochemical potential of Aloe vera and its application as a basis for modern pharmaceutical topical formulations. Results revealed that acemannan increased fibroblast proliferation by up to 200, modulated TGF-1, enhanced type I and III collagen deposition, and accelerated re-epithelialization. Anthraquinones such as aloin and emodin exhibited antibacterial activity against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. Nanoemulsion and nanogel formulations improved transdermal penetration up to threefold compared to conventional gels. These findings highlight Aloe vera’s potential as a wound healing agent and a basis for modern pharmaceutical topical preparations.